The journey of Arabic human rights testimonies, from witnesses to audiences via Amnesty International - Hawker, N (John Benjamins Publishing Company, 2018)
Within the human rights knowledge production infrastructure, information undergoes processes of entextualisation, archiving, publication, and reception. This article examines the place of testimonies – first-person accounts of suffering and/or historic events – in Amnesty International. A network of agents form around testimonies to produce them through translation from the witnesses’ languages – spoken varieties of Arabic – to the language of globalised governance – written English – and to formal written Arabic. The co-construction of meaning, in encounters between human rights researchers and witnesses, is a modern ritual that is entextualised in the genre ‘testimony’; its translations between spoken and written modes, languages and styles, are exercises in persuasive rhetoric aimed at redressing ‘testimonial injustice’. The researchers are not professional translators, yet their unselfconscious translations are constitutive of the knowledge that audiences receive. The data is based on interviews and questionnaires with Amnesty International staff, textual analysis of publications, and on focus groups and surveys.